Variability of Delirium Motor Subtype Scale–Defined Delirium Motor Subtypes in Elderly Adults with Hip Fracture: A Longitudinal Study. Issue 2 (9th December 2016) - Scholtens, Rikie M.; van Munster, Barbara C.; Adamis, Dimitrios; de Jonghe, Annemarieke; Meagher, David J.; de Rooij, Sophia E. J. A.
Abstract : Objectives: To examine changes in motor subtype profile in individuals with delirium. Design: Observational, longitudinal study; substudy of a multicenter, randomized controlled trial. Setting: Departments of surgery and orthopedics, Academic Medical Center and Tergooi Hospital, the Netherlands. Participants: Elderly adults acutely admitted for hip fracture surgery who developed delirium according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, for 2 days or longer (n = 76, aged 86.4 ± 6.1, 68.4% female). Measurements: Delirium Motor Subtype Scale (DMSS), Delirium Rating Scale R98 (DRS‐R98), comorbidity, and function. Results: Median delirium duration was 3 days (interquartile range 2.0 days). At first assessment, the hyperactive motor subtype was most common (44.7%), followed by hypoactive motor subtype (28.9%), mixed motor subtype (19.7%), and no motor subtype (6.6%). Participants with no motor subtype had lower DRS‐R98 scores than those with the other subtypes ( P < .001). The DMSS‐defined motor subtype of 47 (61.8%) participants changed over time. Katz Index of Activities of Daily Living, Charlson Comorbidity Index, cognitive impairment, age, sex, and delirium duration or severity were not associated with change in motor subtype. Conclusion: Motor subtype profile was variable in the majority of participants, although changes that occurred were often related to changes from or to no motor subtype, suggesting evolving or resolving delirium. Changes appeared not be associated with demographic or clinical characteristics, suggesting that evidence from cross‐sectional studies of motor subtypes could be applied to many individuals with delirium. Further longitudinal studies should be performed to clarify the stability of motor subtypes in different clinical populations.